Effects of the γ-secretase inhibitor semagacestat on hippocampal neuronal network oscillation - Hajos, Mihaly; Morozova, Elena; Siok, Chester; Atchison, Kevin; Nolan, Charles; Riddell, David; Kiss, Tamás ‎; Hajos-Korcsok, Eva (Frontiers in Pharmacology, 2013)
Neurological and psychiatric disorders are frequently associated with disruption of various cognitive functions, but development of effective drug treatments for these conditions has proven challenging. One of the main obstacles is the poor predictive validity of our preclinical animal models. In the present study the effects of the γ-secretase inhibitor semagacestat was evaluated in preclinical in vivo electrophysiological models. Recently disclosed Phase III findings on semagacestat indicated that Alzheimer’s disease patients on this drug showed significantly worsened cognitive function compared to those treated with placebo. Since previous studies have shown that drugs impairing cognitive function (including scopolamine, NMDA receptor antagonists and nociceptin receptor agonists) disrupt or decrease power of elicited theta oscillation in the hippocampus, we tested the effects of acute and sub-chronic administration of semagacestat in this assay. Field potentials were recorded across the hippocampal formation with NeuroNexus multi-site silicon probes in urethane anaesthetized male C57BL/6 mice; hippocampal CA1 theta oscillation was elicited by electrical stimulation of the brainstem nucleus pontis oralis. Sub-chronic administration of semagacestat twice daily over 12 days at a dose known to reduce beta-amyloid peptide (Aβ) level (100 mg/kg, p.o.) diminished power of elicited hippocampal theta oscillation. Acute, subcutaneous administration of semagacestat (100 mg/kg) produced a similar effect on hippocampal activity. We propose that the disruptive effect of semagacestat on hippocampal function could be one of the contributing mechanisms to its worsening of cognition in patients with Alzheimer disease. As it has been expected, both acute and sub-chronic administrations of semagacestat significantly decreased Aβ40 and Aβ42 levels but the current findings do not reveal the mode of action of semagacestat in disrupting hippocampal oscillation.